Mechanistic insights into low-dose nZVI-enhanced process stability under variable industrial loads in field-scale anaerobic treatment: Interfacial evolution and strain-resolved adaptation - Zhihong Gao; Lijing Xue; Yujia Ma; Chen Chen; Hong Ling; Lin Wang; Weiming Zhang; Jieshu Qian; Zhichao Yang; Ming Hua; Bingcai Pan (Water Research, 2026)

Iron availability as a time-evolving descriptor linking syntrophic metabolic responses and process performance in nano-iron-amended anaerobic systems - Yujia Ma; Lijing Xue; Zhihong Gao; Chen Chen; Lin Wang; Ming Hua; Zhichao Yang; Chao Shan; Jieshu Qian; Hongchao Li; Weiming Zhang (Bioresource Technology, 2026)

A cascade reaction pathway enabled by sub-micron bismuth-decorated cathode for aqueous Zn-I2 batteries - Zhuoran Ao; Huixin Ren; Yuxi Guo; Lijing Yan; Zhan Lin (Chemical Engineering Journal, 2026)

Multilayer packaging with CO2/O2-selective gas regulation and humidity-responsive release of cinnamon essential oil for cherry tomato preservation - Lin Peng; Jinyu Wang; Lijing Lin; Azadeh Nilghaz; Xueyan Yun; Xiaofang Wan; Shaokai Zhang; Junfei Tian (Food Chemistry, 2026)

Strain-Dominated Pathways of Floating Marine Debris in Xiamen Bay Identified Using Lagrangian Coherent Structures - Haowei Sun; Wenxin Lin; Xiao-Hai Yan; Jianwei Lin; Zishen Li; Lijing Gao; Yuwu Jiang; Xin Zhang (Ocean Modelling, 2026)

Pharmacogenomic screening strategy and indicative screening efficiency for antithyroid drug-induced agranulocytosis in the Southern Han Chinese - Li Ma; Sujie Ke; Peiji Huang; Yao Chen; Qian Lin; Menghua Lin; Guanlian He; Laiyu Zou; Xiaoling Chen; Xiaoying Liu; Libin Liu; Lijing Wang (European Journal of Clinical Pharmacology, 2026)

Effect of maize seed posture on filling performance of a positive-pressure pneumatic seed-metering device with irregular seed-holes - Chong Liu; Lijing Liu; Chunlei Wang; Zhongjun Liu; Donghong Lin; Abdul Mounem Mouazen (Computers and Electronics in Agriculture, 2026)

Synthesis of antioxidant 2-alkynylarylmethyl selenides via three-component assembly of arynes, alkynes and PhSO2SeCH3 - Jiayi Liang; Lijing Wang; Yujie Chen; Jie Hu; Weiqiang Lin; Ge Wu; Wenxi Zhang (Molecular Diversity, 2026)

Quantifying the critical regulator role of irradiation-enhanced electric field in nanoplastics aggregation with heavy metals - Yaowu Zhang; Xianzheng Yuan; Ying Tang; Xinmin Liu; Fengxin Zhao; Yan Peng; Xinping Gao; Lin Wang; Lijing Wang; Rui Tian; Rui Li; Hang Li (Water Research, 2026)

FGF2 Enhances MSCs Secretome Therapy for Skin Photoaging by Delaying Senescence via iNAMPT/AMPK Signaling and Facilitating eNAMPT-Mediated Regenerative Crosstalk - Yixin Zhang; Manping Lu; Jieqing Ouyang; Lin Liang; Fan Li; Zhihan Pei; Lihao Chen; Miaoman Ye; Jiajie Tan; Liwei Xiang; Lijing Kong; Long Huang; et al. (Stem Cell Reviews and Reports, 2026)

Ocean Heat Content Sets Another Record in 2025 - Yuying Pan; Lijing Cheng; John Abraham; Kevin E. Trenberth; James Reagan; Juan Du; Zhankun Wang; Andrea Storto; Karina Von Schuckmann; Yujing Zhu; Michael E. Mann; Jiang Zhu; et al. (Advances in Atmospheric Sciences, 2026)
Global ocean warming continued unabated in 2025 in response to increased greenhouse gas concentrations and recent reductions in sulfate aerosols, reflecting the long-term accumulation of heat within the climate system, with conditions evolving toward La Niña during the year. In 2025, global upper 2000 m ocean heat content (OHC) increased by ∼23 ± 8 ZJ relative to 2024 according to IAP/CAS estimates. CIGAR-RT, and Copernicus Marine data confirm the continued ocean heat gain. Regionally, about 33% of the global ocean area ranked among its historical (1958–2025) top three warmest conditions, while about 57% fell within the top five, including the tropical and South Atlantic Ocean, Mediterranean Sea, North Indian Ocean, and Southern Oceans, underscoring the broad ocean warming across basins. Multiple datasets consistently indicate ocean warming, as measured by 0–2000 m OHC, increased from 0.14 ± 0.03 W m −2 (10 yr) −1 during 1960–2025 to 0.32 ± 0.14 W m −2 (10 yr) −1 during 2005–2025 (IAP/CAS), the latter being consistent with EEI (Earth’s Energy Imbalance) estimates within uncertainties. In contrast, the global annual mean sea surface temperature (SST) in 2025 was 0.49°C above the 1981–2010 baseline and 0.12 ± 0.03°C lower than in 2024 (IAP/CAS; similar in CMA-SST, FY3 MWRI SST, ERSSTv5 and Copernicus Marine data), consistent with the development of La Niña conditions, but still ranking as the third-warmest year on record.

Enhanced photothermal combustion efficiency of propane in the presence of SO2 over Mo-doped Pt/WO3 catalyst: Rational utilization of Ptδ+-(SO4)δ- - Lijing Han; Huimin Chai; Jinliang Lin; Kaiting Chen; Qingwei Li; Qiuhong Zhou; Jun Ye; Hai Liu; Xinyu Han; Zeshu Zhang; Yibo Zhang (Journal of Environmental Chemical Engineering, 2025)

Recent advances in analytical approaches for aroma interaction of fermented foods: A review - Xin Li; Gailing Shi; Jia Zheng; Shuang Xing; Lijing Sun; Shiming Shen; Jian Su; Liangcai Lin; Cuiying Zhang (Food Chemistry, 2025)

Effects of physical exercise on cognitive and motor function in patients with Alzheimer’s disease: a meta-analysis based on randomized controlled trials - Yuxin Gai; Xuelian Dai; Mengyi Qian; Guojian Lin; Piaorou Pan; Tianfu Dai; Yuedan Luo; Lijing Su (Cognitive Neurodynamics, 2025)

Preparation and characterization of ginger essential oil nanoemulsion composite films and its effect on preservation of cherry tomatoes - Peihang Chen; Lijing Lin; Bei Zhang; Qiubian Yang; Jiajia Niu; Sipu Zhang; Jianyin Miao (Food Control, 2025)

Multi-level Priors-Guided Diffusion-based Remote Sensing Image Super-Resolution - Lijing Lu; Zhou Huang; Yi Bao; Lin Wan; Zhihang Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Developments and challenges in external fields-assisted electrocatalysis - Lin Yang; Wei Huang; Lijing Zhang; Yuchao Wang (Chemical Engineering Journal, 2025)

Synergistic inactivation effect of ultrasound and nano-emulsified basil essential oil on the metabolic responses of Salmonella on sprouts - Zifei Liu; Peiwen Sun; Xichen He; Dingsong Lin; Lijing Ke; Chao Shi; Hongshun Yang; Lingchi Deng; Zejia Lin; Lin Chen (International Journal of Food Microbiology, 2025)

Dynamic changes of key metabolites in Longjing green tea during processing revealed by widely targeted metabolomic profiling and sensory experiments - Lin Zeng; Yan-Qing Fu; Ying Gao; Fang Wang; Shuang Liang; Jun-Feng Yin; Marie-Laure Fauconnier; Lijing Ke; Yong-Quan Xu (Food Chemistry, 2024)

Risk assessment of broflanilide for human and non-target terrestrial organisms in cauliflower production - Hongfang Lin; Yuanping Yang; Na Li; Siyu Liu; Lijing Yang; Yu Cheng; Huishan Sheng; Hui Li; Wanting Wen; Yongze Guo; Yuting Zhang (Environmental Research, 2024)

Near-full-length genome analysis of two novel HIV second recombinant forms in Hebei, China - Yuxin Feng; Jianhua Lu; Lijing Wang; Yuling Wang; Jingyun Li; Hanping Li; Lin Li; Erhei Dai (Archives of Virology, 2024)

Physiological and transcriptomic analysis of IAA-induced antioxidant defense and cell wall metabolism in postharvest mango fruit - Yan Zhou; Lei Huang; Shuyi Liu; Miaoyu Zhao; Jiameng Liu; Lijing Lin; Kaidong Liu (Food Research International, 2023)

Exosomal miR-17–92 derived from human mesenchymal stem cells promotes wound healing by enhancing angiogenesis and inhibiting endothelial cell ferroptosis - Wenbo Nie; Xuemiao Huang; Lijing Zhao; Taiwei Wang; Dan Zhang; Tianxin Xu; Lin Du; Yuxiang Li; Weiyuan Zhang; Fengjun Xiao; Lisheng Wang (Tissue and Cell, 2023)

Correction to: Remote sensing drought factor integration based on machine learning can improve the estimation of drought in arid and semi-arid regions - Junyong Zhang; Jianli Ding; Jinjie Wang; Hua Lin; Lijing Han; Xiaohang Li; Jie Liu (Theoretical and Applied Climatology, 2023)

Remote sensing drought factor integration based on machine learning can improve the estimation of drought in arid and semi-arid regions - Junyong Zhang; Jianli Ding; Jinjie Wang; Hua Lin; Lijing Han; Xiaohang Li; Jie Liu (Theoretical and Applied Climatology, 2023)

Mito-TEMPO, a Mitochondria-Targeted Antioxidant, Improves Cognitive Dysfunction due to Hypoglycemia: an Association with Reduced Pericyte Loss and Blood-Brain Barrier Leakage - Lu Lin; Zhou Chen; Cuihua Huang; Yubin Wu; Lishan Huang; Lijing Wang; Sujie Ke; Libin Liu (Molecular Neurobiology, 2023)

Diet-rich in wheat bran modulates tryptophan metabolism and AhR/IL-22 signalling mediated metabolic health and gut dysbacteriosis: A novel prebiotic-like activity of wheat bran - Tao Yan; Lin Shi; Tianqi Liu; Xiangnan Zhang; Minmin Yang; Wen Peng; Xiaomin Sun; Lijing Yan; Xiaoshuang Dai; Xinbing Yang (Food Research International, 2023)

Overexpression of circ_0001445 decelerates hepatocellular carcinoma progression by regulating miR-942-5p/ALX4 axis - Qinhong Xu; Lijing Zhou; Ganghua Yang; Fandi Meng; Yong Wan; Lin Wang; Lei Zhang (Biotechnology Letters, 2020)

The Community Renewal of Shantytown Transformation in Old Industrial Cities: Evidence from Tiexi Worker Village in Shenyang, China - Lijing Dong; Yongchao Wang; Jiayi Lin; Ermeng Zhu (Chinese Geographical Science, 2020)

Determination of biogenic amines in traditional Chinese fermented foods by reversed-phase high-performance liquid chromatography (RP-HPLC) - Xiao Gong; Xiaoxi Wang; Ningli Qi; Jihua Li; Lijing Lin; Zhiping Han (Food Additives & Contaminants: Part A, 2014)

Identification of the Apoptosis Inhibitor Gene p49 of Spodoptera litura Multicapsid Nucleopolyhedrovirus - Mei Yu; Zhaofei Li; Kai Yang; Tiehao Lin; Yingxue Gong; Lijing Pan; Yi Pang (Virus Genes, 2005)